RELEVANSI KOMPETENSI LULUSAN SMK KOMPETENSI KEAHLIAN BISNIS KONSTRUKSI DAN PROPERTI SMKN 1 CIBINONG DENGAN KOMPETENSI YANG DIBUTUHKAN DI DUNIA KERJA - Rananda Ahmad Tauhid, - (2022)
Graduate competence is a graduate's ability qualification that includes attitudes, knowledge, and skills in accordance with agreed national standards. The competence of SMK students basically refers to the competency standards demanded by the industry in accordance with their respective fields of expertise, such as their conformity with the Indonesian National Competency Standards (SKKNI) number 193 of 2021 for the building construction field executive position. This study aims to 1) determine the competence of graduates at SMKN 1 Cibinong, Construction and Property Business Skills Program. 2) Knowing the competencies needed in the world of work according to SKKNI. 3) Knowing the relevance of graduates of SMKN 1 Cibinong Construction and Property Business Expertise Competencies with the world of work. This study uses a descriptive research method with a qualitative approach. The instrument used in this research is a documentation study by collecting sources in the form of letters, documents or photos. The documents used are the syllabus of SMKN 1 Cibinong, competence in construction and property business skills and SKKNI number 193 of 2021 for the position of implementing the building construction field. Based on data analysis, it was found that the description of the competencies possessed by graduates is 82 points and the competencies needed in the world of work according to the SKKNI are 7 points, while the competencies of graduates of SMKN 1 Cibinong, the competencies of construction and property business skills, are not relevant to the competencies needed in the world of work.